2022
DOI: 10.1109/access.2022.3155722
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Attribution of Gross Primary Productivity Increase Over the Mongolian Plateau, 2001-2018

Abstract: Gross primary productivity (GPP) over the Mongolian Plateau (MP) is a vital component of the global terrestrial carbon cycle. Using the latest satellite-based GPP estimates at the best achievable spatial resolution along with several ancillary datasets, we investigated GPP variations in the MP region during 2001-2018 and attributed these changes to land-surface temperature (Ts), total precipitation (Pt), land-cover change (LCC), and atmospheric carbon dioxide (CO2) concentrations. The 18-year-averaged annual c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…Therefore, regional climate characteristics are also an important category of impact factor in GPP prediction. This is also consistent with the conclusions of previous studies [76,77]. Based on the contribution ratio data obtained in this study and the experience of existing studies, it can be considered that EVI, NDVI, P, LULC, Tmax, PET, and ET are the key impact factors for GPP prediction.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, regional climate characteristics are also an important category of impact factor in GPP prediction. This is also consistent with the conclusions of previous studies [76,77]. Based on the contribution ratio data obtained in this study and the experience of existing studies, it can be considered that EVI, NDVI, P, LULC, Tmax, PET, and ET are the key impact factors for GPP prediction.…”
Section: Discussionsupporting
confidence: 92%
“…The GPP and LAI in the foot of the Hangai Mountains, southeast of the Altai Mountains, and other areas were mainly driven by temperature. The areas between Frontiers in Environmental Science frontiersin.org (Bai et al, 2022;Chen et al, 2022). The increase of CO 2 concentration and average precipitation in the Mongolian Plateau from 2000 to 2018 improved soil water supply capacity, enhanced photosynthesis efficiency, promoted vegetation growth, and increased GPP and LAI (Liu et al, 2022).…”
Section: The Climate Factors Driving Gpp and Lai Changes Were Dividedmentioning
confidence: 99%
“…There are multiple indices that can be used to reflect the vegetation changes (Piao et al, 2020). Among these indices, gross primary productivity (GPP) and leaf area index (LAI) can provide useful information to understand changes in terrestrial ecosystems and global carbon budgets in the context of climate change (Bai et al, 2022;Chen et al, 2022). GPP is defined as the carbon absorbed by terrestrial ecosystems through plant photosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of precipitation on greening or browning may be modulated by anthropogenic factors, for example afforestation and land use changes [5,[29][30][31]. It was reported that the greening in China or the increased carbon sequestration in Asian terrestrial ecosystems after 1999 were primarily attributed to the implementation of extensive ecological restoration programs [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%